Retirement-driven dynamic VAR planning for voltage stability enhancement of power systems with high-level wind power - Liu, Junwei (2020)
Conventional VAR compensation devices such as capacitor banks and synchronous condensers, after long periods of service, have become aged and less effective to satisfy stringent requirement of short-term voltage stability in high-level wind power penetrated power systems. STATCOMs with a rapid and dynamic reactive power support capability can be an ideal alternative, when combined with a proper equipment retirement and upgrades scheme. This paper proposes a systematic approach for optimal dynamic VAR resource planning and upgrading for a power system with increased wind power penetration and equipment retirement. The problem is constituted by two parts that are aged equipment retirement and new equipment placement. A multiobjective optimization model is proposed to minimize three objectives: the cost of retirement and upgrades, the index of proximity to steady-state voltage collapse, and the index of transient voltage unaccepted performance. To simulate real-world operating situation, multiple contingencies and uncertain dynamic load models are taken into account. Furthermore, low- and high-voltage ride through abilities for wind farms are modeled. The proposed model is tested on the New England 39-bus test system.